University rankings - are the Philippine HEIs ready for them? - Roman, Emerlinda R. (2012)
This paper first traces the history of university rankings from the US News and World Report, the earliest, to the Times Higher Education rankings, the latest. It questions the validity of such rankings, citing weaknesses in their methodologies and the fact that data can be manipulated. Nevertheless, the author accedes that university rankings are here to stay. The paper then asks if Philippine higher education institutions are ready to be ranked. It contends that since the criteria used by rankers depend much on big financial resources, Philippine HEIs are already at a disadvantage. In addition, there remain inefficiencies in higher education that cause deterioration of the quality of higher education, among which are the high number of HEIs, oversubscribed programs that result in an oversupply of graduates in certain disciplines, and the ten-year preparation for college.
Keywords: Universities and colleges -- Ratings and rankings; Higher education